Management and Role of Guidance and Counseling in Educational Institutions for Personal Development of Students - Haris Haris; Budi Haryanto; Renny Oktafia (International Consortium of Education and Culture Research Studies, 2020)
In order to be able to be independent and develop optimally, counseling is present to provide assistance to students individually or in groups in the personal, learning, social and career fields through various types of services and support activities based on applicable norms. Efforts to help individuals to develop as human beings in terms of education and to form useful personalities in their lives who have various insights, views, interpretations, choices, adjustments and skills appropriate to themselves and their environment, are the role of guidance and counseling in education. To achieve development and optimization in the education process, the form of guidance and counseling is very important.